2020
DOI: 10.1016/j.trsl.2019.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal hsa-miR-21-5p derived from growth hormone-secreting pituitary adenoma promotes abnormal bone formation in acromegaly

Abstract: Growth hormone-secreting pituitary adenoma (GHPA), a benign endocrine tumor located in the base of the skull, results in acromegaly. In addition to the mass effect of the tumor itself in the sellar region, GHPA can lead to the overgrowth of almost every organ. Previous findings indicated that the processes underlying acromegaly were partly attributable to hyperactivity of the growth hormone/insulin-like growth factor-1 (GH/IGF-1) axis. However, the mechanisms driving this syndrome remains largely unknown. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 59 publications
0
17
0
1
Order By: Relevance
“…Subsequently, each condensed supernatant was filtered through a 0.22‐μm filter, and a one‐fifth volume of ExoQuick reagent (EXOTC10A‐1, System Biosciences, USA) was added. Exosomes were isolated using ExoQuick reagent following the manufacturer's recommended protocol 19,20 …”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, each condensed supernatant was filtered through a 0.22‐μm filter, and a one‐fifth volume of ExoQuick reagent (EXOTC10A‐1, System Biosciences, USA) was added. Exosomes were isolated using ExoQuick reagent following the manufacturer's recommended protocol 19,20 …”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, distal tissues can also affect bone tissue by secreting EVs. For example, EVs derived from growth hormone-secreting pituitary adenoma can be internalized by osteoblasts, promoting osteoblast proliferation and bone formation [ 113 ]. These studies have demonstrated that EVs can act as mediators to participate in the biological effects of bone and other tissues.…”
Section: Evs As Potential Mediators Of Psychosocial Stress and Osteoporosismentioning
confidence: 99%
“…Furthermore, the effect is mediated by miRNA regulation of SSTR2 and several miRNAs are known to regulate in the nucleus the transcription of IGF2 and IGF1R. patients where it was highly expressed compared with patients with non-functioning pituitary adenomas (67). MiR-21-5p has been reported to be one of the most abundant in exosomes derived from GH-secreting pituitary adenoma and downregulated the Programmed cell death 4/Activator protein 1 (PDCD4/AP-1) pathway by targeting PDCD4 and SMAD Family Member 7 (Smad7) (67) with subsequent distant effects that have been shown in vitro, specifically osteoblast proliferation, differentiation and mineralization (67).…”
Section: Mirnas Regulating the Gh/igf1 Axis And Igf System In Pituitary Adenomasmentioning
confidence: 99%